Thermal Treatment for the Prevention of Insect Infestation in Dried Fish - Use of a Tunnel Drier/Solar Tent Drier - P., Ravindranathan Nair; T.S., Unnikrishnan Nair; Mathen, Cyriac; K., George Joseph (Fishery Technology, 2025)
A thermal treatment for the prevention of insect infestation in dry fish is described. Â· The treatment was carried out in a tunnel drier/solar tent drier maintained between 55- 65'C. The optimum time of exposure for thin varieties of dry fish was 60 min and 90 min for thick fish. The thermally treated products were packed in polythene bags after cooling. Untreated control had an insect-free shelf life of 1-2 months, whereas the heat-treated controls remained insect-free for 4 months. Refined and preservative treated fish remained insect-free for more than 6 months, while heat treatment further extended the shelf life to more than 12 months.